Solving the conundrum of intra-specific variation in metabolic rate: A multidisciplinary conceptual and methodological toolkit: New technical developments are opening the door to an understanding of why metabolic rate varies among individual animals of a species - Metcalfe Neil B.; Bellman Jakob; Bize Pierre; Blier Pierre U.; Crespel Amélie; Dawson Neal J.; Dunn Ruth E.; Halsey Lewis G.; Hood Wendy R.; Hopkins Mark; Killen Shaun S.; McLennan Darryl; et al. (Wiley, 2025)
Researchers from diverse disciplines, including organismal and cellular physiology, sports science, human nutrition, evolution and ecology, have sought to understand the causes and consequences of the surprising variation in metabolic rate found among and within individual animals of the same species. Research in this area has been hampered by differences in approach, terminology and methodology, and the context in which measurements are made. Recent advances provide important opportunities to identify and address the key questions in the field. By bringing together researchers from different areas of biology and biomedicine, we describe and evaluate these developments and the insights they could yield, highlighting the need for more standardisation across disciplines. We conclude with a list of important questions that can now be addressed by developing a common conceptual and methodological toolkit for studies on metabolic variation in animals.